Nomination typology in the Chinese language (case study of electric power terms) - Zhiyi, Fan (Journal of the Belarusian State University. Philology, 2018)
The article goes into research on the basic models and ways of term structure in the Chinese language, contains the analysis of the structure and semantics features of Chinese terms. The source of terminology includes official papers of NCPE company on Minsk CHPP-2, Minsk CHPP-5, complex construction of the object «NPP construction in the Republic of Belarus» and the list of the most frequently used terminological vocabulary in the electric power industry. Power delivery and communication with energy system» and the list of the most frequently used terminological vocabulary in the electric power industry. The article outlines the ways of formation of terminological vocabulary in the Chinese language, shows the role of terminologization and metaphorization in the process of term formation, depicts the problem of terms synonymy. The article is the first work which investigates terms on the basis of the combinatory semantics theory approach, where a term is considered to be a nominative unit with modifier and actualizer as its main components. The author provides the classification of the Chinese terms based on the number of characters in the term unit. As a result, the author outlines the basic models of term formation in the Chinese language, clarifies the regularities of formation of terminological units of the same type, makes comparison with the Russian equivalents, points out the most productive models of Chinese terminology, proves the high degree of compliance with the basic requirements for terminology. The results obtained can be helpful in the process of compiling the dictionary of electric power terms.